Nitrogen budgeting under the influence of in situ rice residue management options in rice (Oryza sativa)–wheat (Triticum aestivum) cropping system - M, MANU S; SINGH, Y V; SHIVAY, Y S; SHUKLA, LIVLEEN; SHARMA, V K; SAHA, NAMITA DAS; SHEKHAWAT, KAPILA; BANDOPADHYAY, K K; GOUDA, HIMANSU SEKHAR (The Indian Journal of Agricultural Sciences, 2023)
A field experiment was conducted during rainy (kharif) and winter (rabi) seasons 2019–20 and 2020–21 at the research farm of ICAR-Indian Agricultural Research Institute, New Delhi to study the effect of rice establishment techniques (RETs) and microbial consortia mediated in situ rice residue management options on nitrogen (N) budgeting in a rice (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping system (RWCS). The experiment was laid out in split plot design with 3 replications having 2 main plot treatments, viz. aerobic rice (AR) and conventional transplanted rice (CTR) in kharif and 7 sub plot treatments, viz. clean cultivation (removal of paddy straw), paddy straw incorporation, paddy straw mulching, paddy straw incorporation + Pusa decomposer, paddy straw mulching + Pusa decomposer, paddy straw incorporation + urea @20 kg/ha, paddy straw incorporation + Pusa decomposer + urea @10 kg/ha. The residual effects of these treatments were observed in seed drill and zero till sown wheat in rabi seasons. Results showed that N uptake (95.1 kg/ha and 100.4 kg/ha in CTR and 79.4 kg/ha and 83.8 kg/ha in AR) was significantly superior in CTR than AR in kharif seasons. The residual effects of in situ rice residue management options in wheat, paddy straw incorporation + Pusa decomposer + urea @10 kg/ha resulted in significantly higher N uptake (136.4 and 141.5 kg/ha) than other treatments, and it was followed by paddy straw incorporation + Pusa decomposer in both the years. The nutrient uptake by the RWCS was an important indicator of soil fertility and plant nutrient status. This investigation concluded that there is need for use of microbial consortia mediated in situ rice residue management in RWCS for positive N balance in spite of enhanced nutrient uptake.